Analysis of Sociomathematical Norms in Mathematics Learning at 113 Junior High School - Andini Widya Ningsih; Samsul Maarif (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to describe the sociomatematical norms that are owned by students when learning mathematics in class. The subjects of this study were students of class VII-A Jakarta 113 Junior High School. The research method used is descriptive qualitative method. This research uses sociomatematical norms questionnaire and interview. Based on the results of the study, there were 9 students who had very good sociomatematical norms categories with a total percentage of indicators of 81% and there were 14 students who had good sociomatematical norms categories with a total percentage of indicators of 72%. The results showed that very good sociomatematical norms owned by students would affect the high results obtained by students in mathematics learning and good sociomatematical norms would affect the moderate and low results obtained by students in learning mathematics.